Early detection of childhood overweight and related complications in a Danish population-based cohort aged 2–8 years. Issue 3 (May 2022) - Frithioff-Bøjsøe, Christine; Lund, Morten Asp Vonsild; Lausten-Thomsen, Ulrik; Fonvig, Cilius Esmann; Lankjær, Ida Olivia Juhl; Hansen, Tina; Hansen, Torben; Baker, Jennifer Lyn; Holm, Jens-Christian
Abstract: Background: Overweight in early childhood often tracks into adolescence and adulthood and early childhood is a critical period for developing sustained overweight. This study aims to investigate the early detection of childhood overweight (including obesity) and related cardiometabolic complications in a Danish population-based cohort of children aged 2.5–8 years in collaboration with primary care municipal dental clinics and public health nurses. Methods: In this prospective population-based cohort study, 335 pre-school children (age 2.5 and 5 years) were recruited from municipal dental clinics, and 657 school children (age 6–8 years) by public health nurses. A subgroup of 392 children (40%) participated in additional hospital-based examinations including blood pressure measurement and a blood sample. Children were re-examined approximately one year later. Results: The prevalence of overweight was 13.73% in pre-school children and 13.69% in school children at baseline. In the pre-school children, differences in cardiometabolic risk markers between children with and without overweight were minor, whereas in school children with overweight, cardiometabolic derangements were manifest including significantly higher levels of fasting glucose, insulin, homoeostasis model of assessment for insulin resistance, triglycerides, and alanine aminotransferase and lower levels of high-density lipoprotein cholesterol. During follow-up the prevalence of overweight did not change in pre-school children but increased to 17.0% in school children. Conclusions: Existing contacts with the primary health care sector, including dental care, can successfully be used for detection of overweight. This study suggests that early detection should be initiated at pre-school ages since overweight-related complications are already established by school ages.